Call for Special Issue on Equity, Inclusion, and Diversity in Rural Schools and Communities: Resistance in Rural Education - Gallagher, Jennifer L.; Blaisdell, Benjamin; Avent Harris, Janeé; Howard, Christy (Theory & Practice in Rural Education, 2020)
In this special issue of TPRE, we aim to highlight research, teaching, and curriculum that operates as resistance to neoliberal and oppressive educational policy and practice by inquiring into issues of social justice, diversity, equity, and inclusion in rural education.